2014
DOI: 10.1177/014556131409300808
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Neuroma: An Investigation of Associations between Tumor Size and Diagnostic Delays, Facial Weakness, and Surgical Complications

Abstract: We conducted a retrospective case review to ascertain the clinical characteristics associated with acoustic neuromas and their treatment. Our study population was made up of 96 patients—41 men and 55 women, aged 17 to 84 years (mean: 54)—who had undergone treatment for acoustic neuromas and for whom necessary data were available. We compiled data on presenting symptoms, the interval from symptom onset to diagnosis, tumor size at diagnosis, facial weakness, the interval from diagnosis to surgery, the type of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…17 It is established that surgical complications, including facial weakness, CSF leak, and infection, following acoustic neuroma resection are associated with larger tumor size. 6,7 The present findings support this with a trend toward less postoperative steroids in small, nonintracanalicular tumors, though this trend was not statistically significant. Patients with tumors smaller than 1 cm had the lowest incidence of prolonged initial steroid tapers and additional courses.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…17 It is established that surgical complications, including facial weakness, CSF leak, and infection, following acoustic neuroma resection are associated with larger tumor size. 6,7 The present findings support this with a trend toward less postoperative steroids in small, nonintracanalicular tumors, though this trend was not statistically significant. Patients with tumors smaller than 1 cm had the lowest incidence of prolonged initial steroid tapers and additional courses.…”
Section: Discussionsupporting
confidence: 59%
“…Some studies have shown that complication rates following acoustic neuroma surgery vary by tumor size and surgical approach. [5][6][7] The most common complications overall include hearing loss, facial nerve dysfunction, cerebrospinal leak, and postoperative headache. 5 Despite the frequent use of steroids for these complications, there is a paucity of evidence in the literature to indicate that steroids improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the complication of meningitis after operation for acoustic neuroma, the first step is to make an early diagnosis when the acoustic neuroma is still relatively small. Larger tumors are associated with more severe symptoms and surgical complications[27]. Improving surgeon proficiency and strengthening communication and logistics among surgical professionals can reduce the operation time.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, this issue may be more pronounced for immigrants where a lack of access to healthcare or health insurance coverage can further exacerbate diagnostic delays. 24 This can have downstream effects as well because individuals who do not have health insurance coverage are less likely to receive treatment for vestibular schwannomas when compared to their counterparts. 25 Further studies are needed to understand the patient recognition and diagnostic intervals in the immigrant population in the UK.…”
Section: Discussionmentioning
confidence: 99%